Efficiency of the photosynthetic apparatus in Cannabis sativa L. fertilized with sludge froma wastewater treatment plant and with phosphogypsum - Zielonka, Dariusz; Nierebiński, Mariusz; Kalaji, Hazem M.; Augustynowicz, Janusz; Prędecka, Anna; Russel, Stefan (Ecological Questions, 2018)
Sewage sludge and phosphogypsum are by-products of wastewater treatment and phosphorus fertiliser production, respectively. Considering all known methods of their management, it seems rational to use these waste products in agriculture. While assimilating nutrients contained in sewage sludge or phosphogypsum, agricultural crops contribute to the recycling of these otherwise noxious materials. The objective of this study was to identify the effect of fertilization with sewage sludge and with phosphogypsum on selected physiological parameters that determine the efficiency of the photosynthetic apparatus in Cannabis sativa L. Field tests were conducted on three varieties of Cannabis sativa: Białobrzeskie, Tygra and Beniko. Plots were fertilized with sewage sludge as an equivalent of nitrogen nutrition in a dose of 170 kg N.ha-1 and with phosphogypsum applied in three doses: 100, 500 and 1000 kg.ha-1. The plants were subjected to physiological assays (relative content of chlorophyll and leaf area index) on three dates in 2014: 29 June (early development stage), 26 July (full development) and 20 September (final development stage). The study discusses the effect of fertilization with sewage sludge and phosphogypsum on the efficiency of the photosynthetic apparatus in Cannabis sativa.